Jueces, abogados y escribanos: recetario para una construcción relacional de la identidad arequipeña - Coaguila, Jaime F. (Revista de Antropología Social, 2008)
The present investigation proposes an Arequipa´s legal history reconstruction through unofficial discourse of power´s daily negotiations. In this context the escribanos were important figures of the justice administration that participate as intermediaries in the social conflicts, their leading role since the colony implied to be agents of the transformation in the learned modern societies. That is the reason why the escribanos through the writing power were well known out of legal circles, a demonstration of this is the existence of a dish denominated Escribano that tradicionally people eat in the picanterías of Arequipa (Perú) and that has a special anthropological meaning.
Keywords: Arequipa; Identity; Mixed race; Escribano; Legal specialist; Picanterías; Gastronomy; Conflict; Anti power